LEADERSHIP AND SUPERVISION AS CATALYZERS FOR IMPROVING TEACHER COMPETENCE IN FACING THE INDEPENDENT CURRICULUM - Nurmalina; Muhammad Hasyimsyah Batubara; Emy Yusdiana; Khairul Ismi; Irwandi (Program Studi Manajemen Pendidikan Islam, 2026)
The Independent Curriculum requires teachers to be more independent, creative, and responsive to students' needs. However, there are still many teachers who do not have optimal competence in implementing it. This is exacerbated by the leadership of the principal who has not fully played the role of a mentor and motivator and the implementation of academic supervision which is still a formality and has not touched on aspects of professional development in depth. As a result, the process of teachers adapting to the Independent Curriculum is slow and uneven. This research uses a library research approach. The data used in this study were sourced from literature in the form of scientific articles and research reports discussing principal leadership, academic supervision, and teacher competency development. The results of the study indicate that: 1). Principal leadership plays a crucial role in improving teacher competency through support, motivation, and coaching that encourage teachers to be more prepared and capable of implementing the Independent Curriculum. 2). Academic supervision is carried out collaboratively and continuously through classroom observations, feedback, and coaching that helps teachers develop professionalism and understand the Independent Curriculum more deeply. 3). The synergy between leadership and supervision has proven to be an effective catalyst in accelerating teacher competency improvement, especially in adapting to the demands and principles of the Independent Curriculum. Thus, principal leadership and academic supervision have proven to have important and complementary roles in improving teacher competency in facing the Independent Curriculum. Supportive leadership and reflective supervision can create a learning environment that encourages teachers to develop professionally and pedagogically